New insights into the activities and toxicities of the old anticancer drug doxorubicin - van der Zanden, Sabina Y.; Qiao, Xiaohang; Neefjes, Jacques (The FEBS journal, 2021)
The anthracycline drug doxorubicin is an effective anticancer drugs with both DNA‐ and chromatin‐damaging activity. While the chromatin‐damaging activity constitutes major anticancer efficacy of doxorubicin, combination with the DNA‐damaging activity plagues the drug with long‐term toxicities such as cardiotoxicity, therapy‐related malignancies and gonadotoxicity. Therefore, developing DNA damage‐free anthracyclines is a promising direction for novel treatment options with limited side effects, which has been shown to be possible. The anthracycline drug doxorubicin is among the most used—and useful—chemotherapeutics. While doxorubicin is highly effective in the treatment of various hematopoietic malignancies and solid tumours, its application is limited by severe adverse effects, including irreversible cardiotoxicity, therapy‐related malignancies and gonadotoxicity. This continues to motivate investigation into the mechanisms of anthracycline activities and toxicities, with the aim to overcome the latter without sacrificing the former. It has long been appreciated that doxorubicin causes DNA double‐strand breaks due to poisoning topoisomerase II. More recently, it became clear that doxorubicin also leads to chromatin damage achieved through eviction of histones from select sites in the genome. Evaluation of these activities in various anthracycline analogues has revealed that chromatin damage makes a major contribution to the efficacy of anthracycline drugs. Furthermore, the DNA‐damaging effect conspires with chromatin damage to cause a number of adverse effects. Structure–activity relationships within the anthracycline family offer opportunities for chemical separation of these activities towards development of effective analogues with limited adverse effects. In this review, we elaborate on our current understanding of the different activities of doxorubicin and their contributions to drug efficacy and side effects. We then offer our perspective on how the activities of this old anticancer drug can be amended in new ways to benefit cancer patients, by providing effective treatment with improved quality of life.